Development of a web-based sexual risk behavior prevention database with the benefit of 4G LTE by using community participation - Waraporn Boonchieng (2020)
© 2020 Taiwan Academic Network Management Committee. All rights reserved. Sexual risk behavior seems to be a sensitive issue for participants' self-report. This community-based participatory research aimed to develop and validate the web-based sexual risk behavior prevention database for adolescents and their parents in a community in the northern Thailand. It emphasized participation of stakeholders in the community. The process of web-based sexual risk behavior prevention database development included five steps: (1) community partnership formation; (2) draft questionnaire development; (3) psychometric validation; (4) system development, and (5) database evaluation. Both qualitative and quantitative data were collected from March 2015 to March 2016. The findings of this study showed that the sexual risk behavior prevention database was comprised of two parts, including (1) household information which was designed to collect the data regarding household, sexual risk behavior prevention among adolescents, and sexual risk behavior prevention among parents, and (2) data output. Results from implementing the database among adolescents and parents showed that 85% of the adolescents had a boyfriend/ girlfriend and 25% of them engaged in sexual intercourse. For the needs for sexual risk behavior prevention in the community, all of the adolescents and parents suggested providing a campaign to change community member's attitudes towards sexual risk behavior among adolescents. In addition, most of the participants revealed that the use of the web-based sexual risk behavior prevention database with newly 4G LTE wireless network technology where adaptively enhanced features adapted was comfortable and provided a sense of confidentiality, and the data output was helpful for presenting sexual risk behavior situation in the community.